2016
DOI: 10.1038/nnano.2016.242
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility, quantum Hall effect and anomalous optical response in atomically thin InSe

Abstract: A decade of intense research on two-dimensional (2D) atomic crystals has revealed that their properties can differ greatly from those of the parent compound. These differences are governed by changes in the band structure due to quantum confinement and are most profound if the underlying lattice symmetry changes. Here we report a high-quality 2D electron gas in few-layer InSe encapsulated in hexagonal boron nitride under an inert atmosphere. Carrier mobilities are found to exceed 10 cm V s and 10 cm V s at roo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

72
1,091
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,106 publications
(1,213 citation statements)
references
References 31 publications
72
1,091
2
8
Order By: Relevance
“…This is based on observations of their optical properties, which can differ strongly from those of their parent bulk materials, and which have demonstrated room-temperature electroluminesence 28 , strong photoresponsivity 23 with a broad spectral response 26,27,29 , and band gap tunability 24 . Recent studies of luminescence 30 and magnetoluminescence 31 in InSe have shown a strong dependence of the band gap on the number of layers, from ∼ 2.8 eV for the monolayer to ∼ 1.3 eV for thick films. These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is based on observations of their optical properties, which can differ strongly from those of their parent bulk materials, and which have demonstrated room-temperature electroluminesence 28 , strong photoresponsivity 23 with a broad spectral response 26,27,29 , and band gap tunability 24 . Recent studies of luminescence 30 and magnetoluminescence 31 in InSe have shown a strong dependence of the band gap on the number of layers, from ∼ 2.8 eV for the monolayer to ∼ 1.3 eV for thick films. These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of luminescence 30 and magnetoluminescence 31 in InSe have shown a strong dependence of the band gap on the number of layers, from ∼ 2.8 eV for the monolayer to ∼ 1.3 eV for thick films. These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line). The band structure analysis of mono-and few-layer InSe [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has revealed that the conduction and valence band edges near the Γ-point are non-degenerate, being dominated by s and p z orbitals of both metal and chalcogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Among these crystals, InSe has emerged as a semiconducting system with unique electronic and optical properties, including high electron mobility11 and strong photosensitivity 12. Here, we have shown that the formation of crystalline Fe‐islands in InSe induces a uniaxial internal magnetic field (≈1 T) perpendicular to the InSe layers.…”
mentioning
confidence: 82%
“…In this work, we demonstrate magnetic and semiconducting properties in the van der Waals (vdW)‐layered crystal InSe, a material system that has emerged as a promising candidate for electronics11 and photonics12 due to its high electron mobility, chemical stability, and high photoresponsivity. In a vdW crystal, the atoms in each layer are bound by strong covalent bonds, whereas the planes are held together by weak vdW interactions.…”
mentioning
confidence: 98%
“…С целью получения более близ-ких значений E g к результатам измерений оптической ширины запрещенной зоны, в настоящей работе исполь-зовалась систематическая поправка 0.72 eV к энергиям межзонных переходов нанослоев GaTe из расчетов в рамках DFT. Стоит отметить, что аналогичный способ коррекции величин межзонных переходов использовался в [17] для InSe и позволил получить очень хорошее согласие с экспериментом при описании оптических свойств нанослоев селенида индия различной толщины.…”
Section: результаты и обсуждениеunclassified